Anselm's Pursuit of Joy : A Commentary on the Proslogion - Ortlund, Gavin, 1983- (Book collections on Project MUSE., 2020)
"By means of a chapter-by-chapter textual analysis of the Proslogion, Ortlund makes the case that Anselm's goal, far more than an argument for God's existence, is a meditation on God as the chief happiness of the human soul"--